SmCo₅ with a reconstructed oxyhydroxide surface for spin-selective water oxidation at elevated temperature - Chen, Riccardo Ruixi (2022)
The efficiency of electrolytic hydrogen production is limited by the slow reaction kinetics of oxygen evolution reaction (OER). Surface-reconstructed ferromagnetic (FM) catalysts with a spin-pinning effect at the FM/oxyhydroxide interface could enhance the spin-dependent OER kinetics. However, in real-life applications, electrolyzers are operated at elevated temperature, which may disrupt the spin orientations of FM catalysts and limit their performance. In this study, we prepared surface-reconstructed SmCo5 /CoOx Hy , which possesses polarized spins at the FM/oxyhydroxide interface that lead to excellent OER activity. These interfacial polarized spins could be further aligned through a magnetization process, which further enhanced the OER performance. Moreover, the operation temperature was elevated to mimic the practical operation conditions of water electrolyzers. It was found that the OER activity enhancement of the magnetized SmCo5 /CoOx Hy catalyst could be preserved up to 60 °C.